Regional Economic Outlook, October 2010, Middle East and Central Asia. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2010)
The Regional Economic Outlook assesses the near-term outlook for each of the three subregions: the Middle East, North Africa, Afghanistan, and Pakistan (MENAP) oil exporters, the MENAP oil importers, and the Caucasus and Central Asia (CCA). The report also looks at medium-term issues of particular concern to the region, namely the need to boost competitiveness and growth to address high levels of long-standing unemployment in the MENAP region, and enhance the effectiveness of monetary policy and regional cooperation in the CCA.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet